Civil Registers at the Turn of the 20th Century as a Mirror of Language Policy Between the Mura and the Sava River - Lipavic Oštir, Alja; Škafar, Gregor (Slavia Centralis, 2024)
The analysis of the introduction of Slovene into the registers of the Lavantine diocese between 1870 and 1919 shows that German was replaced by Slovene in 92.4% of parishes as a decision of the same parish priest or that of his replacement. In 7.5% of parishes, German was preserved until 1918/1919 (in the form of a linguistic continuum in towns and parishes along the border or close to the border). Individual deaneries partly implemented a language policy regarding language change, however, the dichotomy of town vs. countryside did not decisive a decisive role. The decisive role was played by the individual parish priest and his national commitment, possibly countered only by his own highly developed multilingualism and language switching in everyday life. In this context, the present research allows also for identifying parallels with the introduction of Slovene into education.